Impact of Job Insecurity and Mediation Role Job Satisfaction with Task Performance in Manufacturing Industry Employees in the Era of the Covid 19 Pandemic - Toni Candra; Rojuaniah Rojuaniah (Budapest International Research and Critics University, 2022)
This research aims to explore the negative influence of job insecurity on organizational commitment, job satisfaction, work engagement, and the role of job satisfaction mediation on task performance. In addition, the influence of affective organizational commitment and work engagement on job satisfaction. Furthermore, this study also wanted to confirm the positive influence of job satisfaction on task performance and the role of job satisfaction as a mediator variable that links the influence of job insecurity, affective organizational commitment, and work engagement to task performance, especially for employees of the manufacturing industry. The data collection process was carried out from December 2021 to January 2022 during the Covid-19 pandemic.The research sample was determined using purposive sampling with 150 employees. This study used the structural equation model (SEM) method to analyze the data acquisition. The results found are that job insecurity was proven to reduce affective organizational commitment, job satisfaction, and work engagement. Furthermore, affective organizational commitment can increase job satisfaction. Then, job satisfaction plays an active role in improving task performance. Furthermore, job satisfaction contributes to mediating job insecurity relationships and affective organizational commitment to task performance but cannot mediate work engagement relationships to task performance because work engagement does not influence job satisfaction.